Organizational corruption by public hospitals in China - Tam, Waikeung (Crime, law and social change, 2011)
This article studies the rise of organizational corruption by public hospitals in China since the 1990s and its impacts. Organizational corruption refers to the exploitation of public authority by a government agency for its monetary or material gains. This article argues that a combination of three major factors contributed to the rise of organizational corruption by public hospitals. First, the Chinese government substantially reduced its financial commitment to the health sector since the mid-1980s. To compensate for the retrenchment of government health outlays, public hospitals are authorized to earn revenue, keep and use all budgetary surpluses. This policy provided numerous opportunities and incentives for hospitals to engage in corruption. The second factor concerns the excessive and chaotic development of the pharmaceutical sector. Intense competition has prompted many drug firms to offer bribes to public hospitals so that their products would be purchased. Finally, the state regulatory infrastructure has failed to check the spread of corrupt practices. The study raised two broader implications. First, it highlights the pitfall of retrenchment of government outlays and the subsequent policy of allowing state agencies to generate, retain and use the revenue, in the absence of an effective regulatory infrastructure. Second, the prevalence of organizational corruption indicates that the nature of public hospitals in China has been transformed. Instead of providing efficient, safe and affordable treatment for patients, many public hospitals have engaged in predatory behavior that is harmful to patients’ health.